MICROSTUCTURES AND MAGNETIC PROPERTIES OF BaFe12O19 WITH MgO-Al2O3 ADDITIVES - Eko Arief Setiadi; Fitri Permata Sari; Ayu Yuswita Sari; Ramlan Ramlan; Perdamean Sebayang (Widyariset, 2016)
Barium hexaferrite (BaFe12O19) is a permanent magnet material known as a hard magnet. Microstructures and magnetic properties of MgO-Al2 O3 (0.3 0.9; and 1.5 % mole) addition in BaFe12O19 have been investigated. The mixing powders of Barium Hexaferrite have been prepared by the mechanical alloying method. Particle sizes of the mixing powder show that the particle size increases with the higher concentration of MgO-Al2 O3 additives. The mixing powders are compacted into pellets and sintered with temperatures of 1,100 and 1,200 °C for 2 hours. Herein, X-Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) results show that the samples have a hexagonal structure, and their sizes and shapes are not homogeneous. Hardness values linearly decrease with the increasing of MgO-Al2 O3 (908.58 to 531.81 HV) comparable with bulk density measurements (4.85 to 4.52 g/cm2 ). On the other hand, Paragraph and Gaussmeter measurement shows a decreasing trend as the MgO-Al2 O3 additives content increased. Flux density results decline from 816.00 to 706.20 G, then magnetic remanence decreases from 2.29 to 1.92 kG and saturation magnetization drops from 3.44 to 2.93 kG. In addition, coercivity decreases from 3.83 to 2.52 kOe in proportion to the increasing of sintering temperature.